Understanding inflation in emerging and developing economies - Jongrim Ha; M. Ayhan Kose; Franziska Ohnsorge (Koç University-TÜSİAD Economic Research Forum (ERF), 2019)
Emerging market and developing economies (EMDEs) have experienced an extraordinary decline in inflation since the early 1970s. After peaking in 1974 at 17.3 percent, inflation in these economies declined to 3.5 percent in 2017. Despite a checkered history of managing inflation among many EMDEs, disinflation occurred across all regions. This paper presents a summary of our recent book, "Inflation in Emerging and Developing Economies: Evolution, Drivers, and Policies", that analyzes this remarkable achievement. Our findings suggest that many EMDEs enjoy the benefits of stability-oriented and resilient monetary policy frameworks, including central bank transparency and independence. Such policy frameworks need to be complemented by strong macroeconomic and institutional arrangements. Inflation expectations are more weakly anchored in EMDEs than in advanced economies. In EMDEs that do not operate inflation targeting frameworks, exchange rate movements tend to have larger and more persistent effects on inflation.
Keywords: E31; E42; E52; E58; F62; 330; Prices; Inflation; Monetary Systems; Monetary Policy; Globalization